A LEGAL ANALYSIS OF LAW ENFORCEMENT REGARDING THE ABUSE OF PRESS FREEDOM IN ONLINE MEDIA IN INDONESIA - Lesmana Pranata; Edi Saputra Hasibuan (PT. Altin Riset Publishing, 2026)
The development of digital technology has brought about significant transformations to the press system in Indonesia, particularly through the emergence of online media, which has accelerated the distribution of information and expanded public access. However, this development has also raised various legal issues, such as the spread of unverified news, hoaxes, clickbait, and the potential for abuse of press freedom. This study aims to analyze the legal framework governing press freedom in Indonesia, forms of its abuse in online media, and the roles of the Press Council and law enforcement agencies in resolving press disputes in the digital age. The research method employed is a normative legal approach using legislative and conceptual frameworks. The data utilized includes primary, secondary, and tertiary legal sources, which were analyzed qualitatively through legal interpretation and deductive reasoning. The research findings indicate that press freedom in Indonesia has a strong legal foundation through the 1945 Constitution of the Republic of Indonesia and Law No. 40 of 1999 on the Press; however, in practice, it still faces challenges in the form of regulatory overlap with the ITE Law and the Criminal Code. Furthermore, there is a lack of coordination in the handling of press disputes between the Press Council and law enforcement agencies, which has the potential to create legal uncertainty and lead to the criminalization of the press. The rise of digital media has further exacerbated the situation by accelerating the spread of unverified information and blurring the line between professional journalism and user-generated content. Therefore, regulatory harmonization, institutional strengthening, and improved digital literacy are needed to strike a balance between press freedom and legal accountability in the digital age.